Pengaruh Akut Musik Klasik terhadap Kemampuan Spasial - Leonardo Lubis; Nita Fitria (Majalah Kedokteran Indonesia, 2019)
Introduction: Classical music is a complex melody composition that couldactivate the Brodmann’s area 22, 9, 46, 17, 18, and 19, which are associated inspatial ability as well. Spatial ability is a cognitive function in devising, por-traying, and visualizing an object in space accurately. In the medical field,spatial ability greatly required in learning anatomy, radiograph interpretingand doing the surgical procedure. The aim of this study is to prevail the effectof classical music on spatial ability. Method: An experimental study conducted on the 182 subjects consists of 117female and 65 male medical students. Subjects were divided into two groups,classical music(treatment) group, and silence (control) group. The treatment group listened to Mozart sonata K448 for 10 minutes, while at the very sametime but in a different place, the control group just sat tight for10 minutes aswell. Soon after the 10 minutes, both groups performed the spatial ability test. The spatial test result then analyzed by independent t-test. Result: The spatial score in the treatment group is significantly higher (p less than 0,05)than the control group, both female (33,6379 vs. 31,6949) and male (36,8387vs. 33,9198). Conclusion: Listening to the Mozart sonata K448 could acutely improve thespatial ability